Changes in global gene expression of Vibrio parahaemolyticus induced by cold- and heat-stress. Issue 1 (December 2015) - Urmersbach, Sara; Aho, Tommi; Alter, Thomas; Hassan, Syeda; Autio, Reija; Huehn, Stephan
Abstract Background Vibrio (V .)parahaemolyticus causes seafood-borne gastro-intestinal bacterial infections in humans worldwide. It is widely found in marine environments and is isolated frequently from seawater, estuarine waters, sediments and raw or insufficiently cooked seafood. Throughout the food chain, V. parahaemolyticus encounters different temperature conditions that might alter metabolism and pathogenicity of the bacterium. In this study, we performed gene expression profiling ofV. parahaemolyticus RIMD 2210633 after exposure to 4, 15, 20, 37 and 42 °C to describe the cold and heat shock response. Methods Gene expression profiles ofV. parahaemolyticus RIMD 2210633 after exposure to 4, 15, 20, 37 and 42 °C were investigated via microarray. Gene expression values and RT-qPCR experiments were compared by plotting the log2 values. Moreover, volcano plots of microarray data were calculated to visualize the distribution of differentially expressed genes at individual temperatures and to assess hybridization qualities and comparability of data. Finally, enriched terms were searched in annotations as well as functional-related gene categories using the Database for Annotation, Visualization and Integrated Discovery. Results Analysis of 37 °C normalised transcriptomics data resulted in differential expression of 19 genes at 20 °C, 193 genes at 4 °C, 625 genes at 42 °C and 638 genes at 15 °C. Thus, the largest number of significantly expressed genes was observed at 15 and 42 °C with 13.3 and 13 %, respectively. Genes of many functional categories were highly regulated even at lower temperatures. Virulence associated genes (tdh 1, tdh 2, tox R, tox S, vop C, T6SS-1, T6SS-2) remained mostly unaffected by heat or cold stress. Conclusion Along with folding and temperature shock depending systems, an overall temperature-dependent regulation of expression could be shown. Particularly the energy metabolism was affected by changed temperatures. Whole-genome gene expression studies of food related pathogens such asV. parahaemolyticus reveal how these pathogens react to stress impacts to predict its behaviour under conditions like storage and transport.